Given:
a=b. Applying some basic identity transformations, we get:
a=b
a^2ab=a^2b^2
a(ab)=(a+b)(ab)
a=a+b
a=a+a
a=2a
1=2
With such a proof, we can show that
1=2, pi=E, 10000000000000=1, etc.... Can you spot the flaw?
a=b
a^2ab=a^2b^2
a(ab)=(a+b)(ab)
a=a+b
a=a+a
a=2a
1=2
this is flawed, and since (ab) = 0 (as a and b are equal) it would read correctly as
a=b
a^2ab=a^2b^2
a(ab)=(a+b)(ab)
a(0)=a+b(0)
a(0)=a+a(0)
a(0)=2a(0)
1(0)=2(0)
0=0
i think that is correct ?

Posted by Aim Jayy
on 20021225 22:11:06 